Identification of influencing factors and strategies to improve communication between general practitioners and community nurses: a qualitative focus group study. (26th February 2018) - Nieuwboer, Minke S; Perry, Marieke; van der Sande, Rob; Maassen, Irma T H M; Olde Rikkert, Marcel G M; van der Marck, Marjolein A
Abstract: Background: As the number of patients with complex healthcare needs grows, inter-professional collaboration between primary care professionals must be constantly optimized. General practitioners (GPs) and community nurses (CNs) are key professions in primary care; however, poor GP–CN communication is common, and research into the factors influencing its quality is limited. Objective: To explore patient-related GP–CN communication and facilitating and hindering factors, and to identify strategies to enhance this communication. Method: A qualitative focus group design was used to identify the facilitating and hindering factors and strategies for improvement. In a Dutch primary care setting, 6 mono-professional focus group interviews (3 meetings of 13 GPs; 3 meetings of 18 CNs) were organized between June 2015 and April 2016, recorded and transcribed verbatim. Two independent researchers performed the coding of these interviews, identifying their categories and themes. Results: Results show that, despite the regular contact between GPs and CNs, communication was generally perceived as poor in effectiveness and efficiency by both professions. Mutual trust was considered the most important facilitating factor for effective communication. Profession-specific factors (e.g. differences in responsibility and profession-specific language) and organizational factors (e.g. lack of shared care plans, no in-person communication, lack of time) may be of influence on communication. Participants' suggestions for improvement included organizing well-structured and reimbursed team meetings and facilitating face-to-face contact. Conclusion: GP–CN patient-related communication benefits most from trusting inter-personal relationships. Inter-professional training programmes should address both professional and organizational factors and should be evaluated for their effect on quality of care.